The potential of ligninolytic fungi in bioremediation of contaminated soils - Winquist, Erika (Aalto-yliopisto, 2014)
Soils that are contaminated with the most recalcitrant organic contaminants, such as high molecular weight polyaromatic hydrocarbons (HMW PAH) and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/F), cannot be degraded efficiently by conventional composting. The only available treatment method for these soils, which destroys the contaminants, is combustion at high temperature. This thesis examines three alternative fungal methods to treat these soils: 1) treatment with fungal enzymes, 2) treatment with fungal inoculum, and 3) fungal treatment used as a pre-treatment to improve the energy efficacy in combustion. Manganese peroxidase (MnP), which belongs to lignin-modifying enzymes (LME), was produced and used to treat PCDD/F-contaminated soil in the laboratory scale. Nevertheless, no degradation with a MnP preparation was observed, although a substantial amount of MnP activity was found in the soil still after 10 days of incubation. Both PAH- and PCDD/F- contaminated soils were treated with fungal inoculum in the laboratory scale. HMW PAHs were degraded significantly more by the fungi than by the indigenous microbes alone in the laboratory experiments, where the PAH concentration of soil was 3500 mg kg -1 (sum of 16 PAH). Treatment with Phanerochaete velutina (inoculum) resulted to degradation of 96 % of 4- ring PAHs and 39 % of 5- and 6-ring PAHs in three months. With PCDD/F-contaminated soil, no degradation was observed in the control, but the degradation of PCDD/Fs with fungal treatments was significant ( P. velutina : 62 %, Stropharia rugosoannulata : 64 % of WHO-TEQ value). Fungal treatment of PAH-contaminated soil was also applied in the field scale (2 t). However, both P. velutina (inoculum) and control treatment resulted in equal degradation in soil with lower PAH concentration (1400 mg kg -1 , sum of 16 PAH): 94 % of the 16 PAHs were degraded in three months. Fungal treatment was even applied as a pre-treatment for contaminated soil with high organic matter content, and which will be later combusted. In the pilot-scale (300 kg), 13 % degradation of the original organic matter content was obtained in 6 months. To conclude, fungal treatment is reasonable to apply for soils with organic contaminants that cannot be bioremediated by composting. With soils contaminated by chlorinated dioxins, this is always the case, but also PAH-contaminated soils with high total concentration or high proportion of HMW-PAHs. In addition, with fungal treatment the amount of organic matter in the soil can be reduced and the efficacy of the combustion process is improved.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; bioremediation; fungi; lignin-modifying enzymes; polyaromatic hydrocarbons; biologinen puhdistus; sienet